Detection of Motorcycle Tire Endurance based on Tire Load Index using CNN - Birawa Kaca Buana Gora; Nugroho Tegar Maulana; Muhamad Novan Aulia Zam Zami; Anan Nugroho; Alfa Faridh Suni (DoubleClick: Journal of Computer and Information Technology, 2023)
With increasingly rapid technological developments, the production of motorized vehicles will increase with the use of robotic power in production. The increasing number of motorized vehicles in big cities does not escape the rise of traffic accidents that occur. One aspect of accidents that we usually underestimate is the resistance of our vehicle tires to support the load on the vehicle. Therefore, we need a system to detect the resistance of a tire in supporting the load on the vehicle. For this reason, this study was conducted to detect the durability of motorcycle tires based on tire load index using a convolutional neural network. A 70% result was found in classifying tire resistance based on tire load index.